Case Study Analysis of Substance Abuse in Schools within Critical Social Work Practice - KÜÇÜKOBA, Ercan (Indonesian Journal of Social Science Research, 2025)
The research, "Case Study Analysis of Substance Abuse in Schools within Critical Social Work Practice," examines the complexity of substance abuse among students within a social work framework. It highlights how social, economic, and psychological factors contribute to students’ substance use, especially for those from disadvantaged backgrounds. Through Alex’s case, the study illustrates how family instability and socio-economic hardships can lead to substance abuse as a coping mechanism. The paper advocates a critical social work approach, grounded in Marxist theory, humanism, and critical thinking, to address systemic issues influencing substance use. This approach emphasizes a shift from punitive measures to supportive interventions within schools and communities, including collaboration with families and policy advocacy. By focusing on socio-economic determinants and the need for structural change, the study provides a framework for creating supportive educational environments that address the root causes of substance use and promote positive behavioral change among students.